Relative toxicity of different combinations of temephos and fenthion with Solanum xanthocarpum extract against anopheline larvae. Issue 4 (15th July 2013) - Mohan, Lalit; Sharma, Preeti; Shrankhla,; Srivastava, Chand Narayan
Abstract: The relative toxicity of different concentrations of temephos and fenthion with petroleum ether root extract of Solanum xanthocarpum (Schrader) at 1 : 1, 1 : 2 and 1 : 4 ratios was evaluated against Anopheles stephensi (Liston) larvae. All combinations exhibited antagonism at concentrations lower than LC50 values and synergism at concentrations higher than their LC90 values. A 1 : 1 product ratio was the most effective.